Early predictive efﬁcacy of core antigen on antiviral outcomes in genotype 1 hepatitis C virus infected patients - Feng,Bo (2015)
Response-guided therapy is of limited use in developing countries because hepatitis C virus RNA detection by sensitive molecular methods is time- and labor-consuming and expen- sive. We evaluated early predictive efﬁcacy of serum hepatitis C virus core antigen kinetics on sustained virologic response in patients with genotype 1 hepatitis C virus during pegylated interferon plus ribavirin treatment. For 478 patients recruited, hepatitis C virus RNAs were detected at baseline, and at weeks 4, 12, 24, 48, and 72 using Cobas TaqMan. Architect hepatitis C virus core antigen was performed at baseline, and weeks 4 and 12. Predictive values of hepatitis C virus core antigen on sustained virologic response were compared to hepatitis C virus RNA. In the ﬁrst 12 weeks after treatment initiation the dynamic patterns of serum hepatitis C virus core antigen and hepatitis C virus RNA levels were similar in sustained virologic response, relapse, and null response patients groups. Although areas under the receiver operating characteristics curves of hepatitis C virus core antigen were lower than those of hepatitis C virus RNA at the same time points, modeling analysis showed that undetectable hepatitis C virus core antigen (rapid virological response based on hepatitis C virus core antigen) had similar positive predictive value on sustained virologic response to hepatitis C virus RNA at week 4 (90.4% vs 93.3%), and hepatitis C virus core antigen decrease greater than 1 log10 IU/mL (early virological response based on hepatitis C virus core antigen) had similar negative predictive value to hepatitis C virus RNA at week 12 (94.1% vs 95.Z%). Analysis on the validation group demonstrated a positive predictivevalue of 97.5% in rapid virological response based on hepatitis C virus core antigen and a negative predictive value of 100% in early virological response based on hepatitis C virus core antigen. In conclusion, hepatitis C virus core antigen is comparable to hepatitis C virus RNA in predicting sustained virologic response of chronic genotype 1 hepatitis C virus infected patients, and can be used to guide anti-hepatitis C virus treatment, especially in resource-limited areas.